Understanding social research - Dale, Angela; Mason, Jennifer (London ; Thousand Oaks, Calif. : SAGE, 2011)
What is the relationship between methodology and the messy reality of everyday research in action? How do we make arguments about the social world on the basis of our research? How is the knowledge that research produces shaped by the methods we use?
Understanding Social Research examines the core principles that inform the process of doing research and being a social researcher in the 21st century. It does so by looking at the creative tensions that lie at the heart of all social research and the interplay between research design, theory, method and our real-life research subjects and experiences.
Mason and Dale have brought together leading researchers from across the social sciences, including Sociology, Health, Geography, Psychology and Social Statistics, to explain how they approach research design and practice, and to consider what kinds of knowledge their methods can produce when applied in real life research. In so doing, this book examines a wide range of state-of-the-art approaches to doing research, and examines them in the context of three core sets of social issues; personal life and relationships, social change, and the role of place. Such cross currents are drawn together skilfully by the editors so as to get inside the heart of how we think about and conduct research today.
Keywords: Social sciences; Social sciences; Empirische Sozialforschung; Forschungsmethode